2012
DOI: 10.1186/2045-3329-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of published phase I/II clinical trials between 1990-2010 in osteosarcoma and Ewing sarcoma confirms limited outcomes and need for translational investment

Abstract: BackgroundHigh grade primary bone sarcomas are rare cancers that affect mostly children and young adults. Osteosarcoma and Ewing sarcoma are the most common histological subtypes in this age group, with current multimodality treatment strategies achieving 55-70% overall survival. As there remains an urgent need to develop new therapeutic interventions, we have reviewed published phase I/II trials that have been reported for osteosarcoma and Ewing sarcoma in the last twenty years.ResultsWe conducted a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 77 publications
0
31
1
Order By: Relevance
“…Over the last decade, technological advances in research and medicine have provided detailed descriptions of factors that contribute to the malignant phenotype of this disease with the hope of finding new therapeutic treatments and strategies. The recent review of van Maldegem et al (2012) of published clinical trials for OS shows that most phase III trials are combination treatments of conventional chemotherapy agents. Many biological based treatments evaluated in the PPTP and phase I and II trials have yet to advance to phase III trials.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, technological advances in research and medicine have provided detailed descriptions of factors that contribute to the malignant phenotype of this disease with the hope of finding new therapeutic treatments and strategies. The recent review of van Maldegem et al (2012) of published clinical trials for OS shows that most phase III trials are combination treatments of conventional chemotherapy agents. Many biological based treatments evaluated in the PPTP and phase I and II trials have yet to advance to phase III trials.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial improvements in surgery and chemotherapy have increased the survival rate of patients with localized disease. However, the prognosis of patients with metastatic or recurrent disease is still poor owing to the lack of second-line chemotherapies (4)(5)(6). This necessitates the development of better and safer chemotherapeutic strategies against osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported significant advances in adjuvant chemotherapy for osteosarcoma (1,2), however, in the last two decades, treatment outcomes for patients with osteosarcoma have not improved sufficiently, despite the implementation of several new therapeutic interventions. In a comprehensive analysis of published phase I/II clinical trials, researchers found that effective drugs tended to have high toxicity (3). Therefore, new therapeutic strategies for the treatment of osteosarcoma are needed.…”
Section: Introductionmentioning
confidence: 99%